الذكاء الإستراتيجي وأثره على صناعة وإتخاذ القرارات الإستراتيجية. دراســــة ميدانية على مصـــــرف الجمهــــوريـــة الرئـيسي (Comprehensive Journal of Science, 2025)
The shift towards strategic intelligence is a modern trend that enhances organizational capabilities across various dimensions. It has recently garnered significant attention at the local، regional، and international levels as an effective means of achieving organizational goals and assisting different management levels in decision-making. This research aims to define the conceptual framework of strategic intelligence and strategic decisions، and the nature of their impact، in its various dimensions، on strategic decision-making. The researcher employed a descriptive-analytical approach، along with the SPSS statistical software، to analyze and interpret the data. The research yielded several key findings، most notably: the leadership of the Republic Bank conducts in-depth studies of strategic decisions and their outcomes before making any strategic decision، through a comprehensive، objective، and clear scientific planning process for all their operations. A set of recommendations was also developed، the most important being the necessity for the Republic Bank's leadership to study the external environment، seize available opportunities، and mitigate anticipated threats.Development.